JKN participation in accessing health services during the COVID-19 period in Sleman Regency (secondary data analysis of HDSS 2020) - Septiani, Trisna; Hafidz, Firdaus (Universitas Gadjah Mada, 2022)
Purpose: Participation in JKN (Jaminan Kesehatan Nasional) is one of the factors that has a positive effect on healthcare utilization. The utilization of JKN has continued to increase, reaching 276.1 million visits in 2019. However, the COVID-19 pandemic has caused disruptions in the utilization of healthcare. Visits to health facilities are reported to have decreased, with 224.7 million visits in 2020. This research aims to describe utilization patterns based on the type of health facilities visited and determine the relationship between JKN participation and other factors on health service utilization during the COVID-19 pandemic. Methods: Descriptive analytical study with a cross-sectional design using secondary data from the Health and Demography Surveillance System (HDSS) 2020 cycle 6. The quantitative data analysis was conducted using univariate, bivariate, and multivariate analyses. Results: 69.77% of respondents used healthcare, while 30.23% did not. Other health facilities, particularly pharmacies, were the most commonly used choices by respondents to address their health problems. Not being sick enough to receive treatment (83.94%) and fear of contracting COVID-19 (11.92%) were the primary reasons respondents cited for not accessing healthcare. There was no significant correlation between the variables of JKN involvement, age, gender, education level, marital status, economic status, and residence location and the use of healthcare services (p > 0.05). The most critical variable was a history of NCD (p<0.05). Conclusion: The need factor, combined with the history of NCD, is the primary predictor of health service utilization among the people of Sleman Regency during the COVID-19 pandemic.